Solution of Fisher’s equation using Integral iterative method / Mat Salim Selamat ... [et al.] - Selamat, Mat Salim; Zakaria, Nursyaqila; Mahrop, Siti Aisyah; Raja Azman Shah, Raja Iryana Puteri (Universiti Teknologi MARA, Negeri Sembilan, 2022)
In general, partial differential equations play an important role in various fields of science and engineering. The main problem that researchers focused on is solving the nonlinear part of the differential equation. Fisher’s equation is an example of a nonlinear differential equation. Fisher’s Equation (FE) is a reaction-diffusion equation in the context of population dynamics. IIM is considered as one of the simple methods to solve FE because this method generates a sequence of approximations. Furthermore, this method is applied for both linear and non-linear problems that contain a large number of variables. However, the accuracy of IIM results only applicable for a small time domain t.